Diferensial Parsial dan Trend Penjualan dalam Analisa Kontribusi Margin untuk Menentukan Sales Mix yang Optimal - Rustam Hanafi (AKSES: Jurnal Ekonomi dan Bisnis, 2006)
The research was held to know : (1)  How type of each  product variable cost  which applied in many company  (2) How many products that must be sold from each of them for optimal composition (3) how the value of profit optimum. From the research on Dipta Sunrise Nusantara II Company which product many export shoes,  was known that that variable cost on each product made square equation or  Curve line.  From this point, the variable had point optimum which could  influence margin contribution. With Differsial Parsial   on margin contribution  was yield optimum sales for type GOLA shoes 107.156 set, LETOON 107.180 set, UNIVERSE 82.552 set and minimize sales for GOGGI shoes 117.371 set and CATALPA 107.249 set. Maximize sales as the demand for GOGGI was 120.500 set and CATALPA 114.000 set. From the research, we could know that optimum supplier composition from each product to optimum profit were : GOLA 107.156 set, GOGGI 120.500 set, CATALPA 114.00 set, LETOON 107.180 set and UNIVERSE 82.552 set. So total optimum profit from    these were Rp 8. 708.080.000,00